The Rhythm of Death. Seasonality of Mortality in Amsterdam, 1812–1931 - Buzasi, Katalin; Riswick, Tim (Historical Life Course Studies, 2025)
Between 1812 and 1931, Amsterdam experienced profound demographic, social, and epidemiological changes that reshaped how, when, and why people died. By tracing seasonal mortality patterns over this time period, trends in the rhythm of death are explored in our study. Using monthly death counts from municipal yearbooks and the Amsterdam Cause-of-Death Database, and applying wavelet power spectrum analysis, we identify both persistent winter excess mortality and key disruptions caused by epidemics. For the period 1856–1891, for which continuous cause-specific data is available, our findings reveal that, although airborne infectious diseases largely shaped the winter mortality peak, excess winter deaths remained evident even after their removal. This suggests the important role of other causes-of-death, such as cardiovascular diseases, which are caused by other factors than seasonal viruses. Beyond these findings, it is argued that environmental exposures, such as temperature and reduced sunlight, alongside social inequalities in shaping seasonal vulnerability should be taken into account in future research.